Quality of life and stimulus perception in patients' rehabilitated with complete denture - Goiato, Marcelo Coelho [UNESP]; Bannwart, L. C. [UNESP]; Moreno, A. [UNESP]; Santos, Daniela Micheline dos [UNESP]; Martini, A. P. [UNESP]; Pereira, L. V. [UNESP] (Wiley-Blackwell, 2012)
The objective of this study was to evaluate and correlate quality of life (QoL), and stimulus perception of complete denture users, before and after the insertion of new prostheses. We selected 60 patients using bimaxillary complete conventional dentures who needed to replace their prostheses. During anamnesis, we collected demographic data and applied the Oral Health Impact Profile for Edentulous Patients (OHIP-EDENT) questionnaire and stimulus perception questionnaire (PERCEPTION). Before installation of new prostheses, the patients responded to OHIP-EDENT questionnaire, and on the day of installation, they responded to PERCEPTION questionnaire. At the patients 3-month follow-up, we re-administered the OHIP-EDENT and PERCEPTION questionnaires. The Wilcoxon and MacNemar tests were used to compare patient responses between the time points analysed. Most of the OHIP-EDENT items showed a highly significant impact of the new prostheses on oral health (P = 0.003). The PERCEPTION questionnaire data indicated that the patients experienced significant improvements (P < 0.05) in terms of their sensations with the new prostheses. Cross-lagged data analysis did not show any causality between the OHIP-EDENT and PERCEPTION questionnaires (ZPF test, P = 0.772). We concluded that the treatment was effective with respect to the patients QoL and their adaptation to the new prostheses.
Keywords: oral health-related quality of life; oral health impact profile; complete dentures patient satisfaction; questionnaires